POTENTIAL FOR DEVELOPING PHYTOPHARMACY BASED ON MARINE RESOURCES: REVIEW - Zebua, Ratna Dewi; Waruwu, Eliyunus; Telaumbanua, Betzy Victor; Laoli, Destriman (Asian Journal of Aquatic Sciences, 2023)
Indonesia is the world's largest archipelagic country, providing abundant biodiversity potential. The rapid development of chemistry, phytochemistry, and pharmacology has increased the research and application of various plants in the health sector. Phytopharmaca is a standardized herbal medicine that has proven its efficacy through clinical trials. Various types of marine biota that are easy to find have been proven to contain bioactive compounds that can potentially develop phytopharmaceuticals based on biological resources. The development of phytopharmaceuticals made from marine plant raw materials has yet to be widely developed. Limiting factors often found are references to pharmaceutical standardization and the required research funding. However, this does not rule out the possibility of realizing phytopharmaceutical products from marine plants that meet standards and clinical trials. Therefore, the aim of the explanation regarding research, types, and potential of marine biological resources in phytopharmaceuticals is to provide information and learning media.